Pengembangan Aplikasi Project Simulasi Limit Fungsi Mengunakan Matlab - Farah Heniati Santosa; Samsul Bahri; Malik Ibrahim (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
This study aims to produce a project application in the form of a limit simulation simulation media that functions valid, practical and effective. The development model uses 4D (Define, Design, Develop, Disseminate). Analysis of expert assessment, implementation of instructional media, and student response after using learning media with student achievement analysis using one way anova. The result concluded that (1) the learning media of limit function simulation is valid based on the assessment of experts with score 4,174. (2) limit simulation media is stated to be practical in learning with a practicality score of 85% which is in a very good category. (3) instructional media of effective function limit simulation is based on student achievement using learning media better than students who do not use it. The average score of student achievement in the experimental class is 76.25 while the average score of student achievement in the control class is 64.75.